The diagnostic accuracy of O-(2-18F-fluoroethyl)-L-tyrosine parameters for the differentiation of brain tumour progression from treatment-related changes. Issue 3 (March 2022) - Diao, Wei; Su, Dunyan; Cao, Yuan; Jia, Zhiyun
Abstract : Background: 18 F-fluoro-ethyl-tyrosine ( 18 F-FET) is recommended to distinguish brain tumours post-therapeutic true progression (including recurrent and metastatic brain tumours) and treatment-related change (TRC). However, many parameters of 18 F-FET can be used for this differential diagnosis. Our purpose was to investigate the diagnostic accuracy of various 18 F-FET parameters to differentiate true progression from TRC. Methods: We performed a literature search using the following databases: the PubMed, Embase and Web of Science databases up to 29 November 2020. We included studies that reported the diagnostic test results of 18 F-FET to distinguish true progression from TRC. The Quality Assessment of Diagnostic Accuracy Studies-2 tool was used to evaluate the quality of the included studies. The diagnostic accuracy of various parameters was pooled using a random-effects model. Results: We included 17 eligible studies (nine parameters). For static parameters of 18 F-FET, the maximum and mean tumour-to-brain ratios (TBRmax and TBRmean ) showed similar pooled sensitivities of 82% [95% confidence interval (CI), 80–85%) and 82% (95% CI, 78–85%), respectively. Among the three kinetic parameters (slope, time to peak and kinetic pattern), the kinetic pattern presented the optimal diagnostic value with a pooled sensitivity of 81% (95% CI, 75–86%). When combining the static and kinetic parameters, the diagnostic performance of 18 F-FET was significantly improved, with a pooled sensitivity of 90% (95% CI, 84–94%) in the combination of TBR and kinetic patterns. Conclusions: 18 F-FET static parameters alone showed a comparably high sensitivity in the differentiation between brain tumour true progression and TRC. Combining static and kinetic parameters provided improved diagnostic performance. Abstract : Supplemental Digital Content is available in the text.